Intense red upconversion emission in infrared excited holmium-doped PbGeO3-PbF2-CdF2 transparent glass ceramic - Neto, A. S.; da Costa, E. B.; Bueno, L. A.; Ribeiro, SJL (Elsevier B.V., 2004)
Intense red upconversion emission around 650 nm in PbGeO3-PbF2-CdF2 transparent glass ceramic containing beta-PbF2:Ho3+ nanocrystals, is presented. The holmium-doped vitroceramic samples were excited by a 980 nm diode laser source. The 650 nm upconversion signal was assigned to the F-5(5) --> I-5(8) transition of holmium ions. Very low intensity signals around 490 and 540 nm corresponding to the F-5(2,3) --> I-5(8) and S-4(2), F-5(4) --> I-5(8) transitions, respectively, were also detected. The upconversion excitation mechanism was achieved through a combination of stepwise phonon-assisted multiphoton absorption, cross-relaxation processes involving pairs of holmium ions, and excited-state absorption. Using a diode laser pump source around 850 nm green upconversion emission around 540 nm was the observed predominant signal. (C) 2004 Elsevier B.V. All rights reserved.
Keywords: vitroceramic; holmium; upconversion; luminescence; energy-transfer